What is the contribution of food self-provisioning towards environmental sustainability? A case study of active gardeners - Vávra, Jan; Daněk, Petr; Jehlička, Petr (Elsevier SCI LTD, 2018)
Food self-provisioning, also labelled as household food production, is a traditional activity persisting in the countries of the Global North. Recently, it has become an object of sustainability oriented research due to the positive social, health and environmental outcomes. However, little is known about the rate of self-sufficiency of the food self-provisioners and about environmental context of this kind of food production, including its actual potential for the reduction of greenhouse gas emissions. To clarify these topics, we analysed sociological data from a quantitative research study carried out in the Czech Republic in 2015. The data from 775 food growing households were used. The combined rate of self-sufficiency of the households was calculated as the share of home grown fruit, vegetables and potatoes in the overall consumption of the household. The rate of self-sufficiency (33%) was then compared with average food consumption and multiplied by the different values of greenhouse gas emissions reduction potential of home grown food. This led to the reduction of 42–92 kg CO2eq/person/year, which constitutes 3–5% of overall food emissions of Czech households. The research shows that positive environmental effects are not negatively counterweighted either by excessive use of industrial fertilisers or by car transportation to the gardens. Environmental motivation is unimportant for gardeners. Our findings give support to “quiet sustainability” and “sustainable materialism”, two recently advanced concepts highlighting the importance of considering everyday practices in the quest for sustainability.
Keywords: Alternative food networks; Carbon footprint; Food self-provisioning; Gardening; Greenhouse gas emissions; Self-sufficiency